Persistence and Loss of Cultural Values of Tiriki Sacred Groves in Hamisi District, Kenya: Implications for Management - Fredrick Nyongesa Kassilly; Harrison Mugatsia Tsingalia (Cutting Edge Research in Biology Vol. 7, 2023)
The present study aimed to investigate the Persistence and Loss of Cultural Values of Tiriki Sacred Groves in Hamisi District, Kenya. The loss of cultural values and locals’ protection for Tiriki sacred groves was linked to the neglect and vandalism the authors observed during their casual visits in January 2007. Between March and August 2007, 65 randomly chosen key informants (51 men and 14 women) from all six locations in Kenya’s Hamisi district participated in household interviews. The goal of the study was to ascertain whether or not local residents still adhere to the traditional cultural values of the groves, as well as the causes of each cultural value’s loss. Of the 10 traditional values named, the most dominant was as sources of herbal medicine (100%) and as sites for boys’ circumcision (100%). The least dominant were as sources of food (13.85%) and materials for house construction (21.54%). Persistence was highest with their value as sources of herbal medicine (100%) and lowest as burial sites for community heroes (0.00%) and as sites for special prayers (4.17%). Break-down in the socio-cultural fabric of the Tiriki community due to the influence of modern religion, education and government regulations were responsible for loss of cultural values and indigenous knowledge associated with sacred groves among local people. The strategic government intervention necessary for the sacred groves’ sustainable preservation, along with the appropriate institutional framework, will enable the local population to manage and profit from them. The Millennium Development Goals’ emphasis is on businesses that combine biodiversity conservation and poverty eradication. In order to achieve this, the creation of local, regional, and international partnerships is encouraged.